MENYELAMI FIQIH MADZHAB MALIKI (Karakteristik Pemikiran Imam Maliki dalam Memadukan Hadits dan Fiqih) - Abdurrohman Kasdi (Program Studi Hukum Keluarga Islam, 2017)
Imam Maliki is one of the Imam of the Four Schools who has great influence in some areas of Islam. The characteristic that became one of Imam Malik's privileges was that he was a figure in fiqh and hadith. With this mastery of science and method of ijtihad, Imam Malik became a famous scholar in the hemisphere, people from every corner came to him and they jostled in his majlis and gathered to study. He gave fatwas and taught people about 70 years old. The scholars agree on his character, glory, religion, wara ', and grip against the sunnah. There are several characteristics in the jurisprudence of the Maliki School of Islam that make the method special, which influences the development of the Maliki School and makes it different amongst him and other scholars: First, the Maliki School of Medina holds the Meditative deed because Medina is the place of the Messenger of Allah. Secondly, he made mashalih al-mursalah as a source of law. Mashalih al-mursalah are things that aim for human benefit, but not specified by the shari'ah in particular. Third, Imam Malik clings to the fatwas of the sahabah (qaul sahabi) because they are the forerunner of the hijrah with the Prophet or the aid class (Ansor). Fourthly, Imam Maliki uses Istihsan in various problems, such as employee guarantees, helping the owner of the bread kitchen and the mill, the pay of the bathroom for everyone is the same and the implementation of qisas which should present some witnesses and oaths. Fifth, a special sunnah position before Imam Malik.